2020
DOI: 10.19053/01217488.v11.n1.2020.10973
|View full text |Cite
|
Sign up to set email alerts
|

Common Reactions of Furfural to scalable processes of Residual Biomass

Abstract: Energy and the environment will always play key roles in society. The climate emergency cannot be ruled out to enable the transition for a clean energy future. Currently, non-renewable energy resources are declining, therefore is important to continuously explore renewable resources. Biomass is a renewable resource that can be applied to reduce climate changes and to accomplhish emission policies. Cellulose is the most abundant type of biomass worldwide, which can be transformed into biofuels and potential bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Among the information analyzed from Colombia, a review was found describing the processes for obtaining FF from RLB and the reactions to convert it into molecules of interest. For example, hydrogenation to generate furfuryl alcohol and oxidation to obtain maleic acid, furoic acid, and methyl furoate (Rodriguez et al, 2020 ). Laverde et al ( 2019 ) reported an interesting route in which they used oil palm pulp, since it has a high content of cellulose and hemicellulose.…”
Section: Introductionmentioning
confidence: 99%
“…Among the information analyzed from Colombia, a review was found describing the processes for obtaining FF from RLB and the reactions to convert it into molecules of interest. For example, hydrogenation to generate furfuryl alcohol and oxidation to obtain maleic acid, furoic acid, and methyl furoate (Rodriguez et al, 2020 ). Laverde et al ( 2019 ) reported an interesting route in which they used oil palm pulp, since it has a high content of cellulose and hemicellulose.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26] As one of the key bio-based molecules, the global production of furfural in 2019 reached $551 million (USD) and is estimated to exceed $700 million by 2024. 27,28 With the wide accessibility and low cost ($1500 per ton) of furfural, the cascade Diels-Alder (DA) cycloaddition and aromatization of furfural derivatives has gradually become a significant pathway to synthesize renewable aromatics, particularly functionalized aromatic compounds. 19,29 Furfural is rarely used for direct DA cycloaddition because aldehyde as an electron-withdrawing group stabilizes the HOMO of the furfural molecule, leading to the increase of the HOMO-LUMO energy gap between the furfural and dienophile and thus the inhibition of cycloaddition.…”
Section: Introductionmentioning
confidence: 99%
“…Furfural is a compelling substrate among numerous platform chemicals derived from pentoses due to its established commercial production (280–400 kton/year). , The global furfural market has been expanding rapidly, with the market size growing from USD 551 million in 2019 to an estimated USD 700 million by 2024. However, other potential derivatives such as 2-furoic acid (FURA), 2-methyl furan (2-MF), tetrahydrofurfuryl alcohol (THFA), tetrahydrofuran (THF), and 2-methyl tetrahydrofuran (MTHFA) can also be produced from furfural …”
Section: Introductionmentioning
confidence: 99%